The level of connectivity at transfer stations for rail-transit in Kuala Lumpur City Centre - Muanati Afzan Mohammad, 1987-; Muhammad Zaly Shah Muhammad Hussein; Fakulti Alam Bina (2010)
Project Paper (Sarjana Muda (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2010